Perencanaan Pit Limit Penambangan Blok D dengan Optimasi Nilai Net Present Value Pada PT Bumi Indo Power Kabupaten Tanjung Jabung Barat Provinsi Jambi - Yulanda, Yudi Arista (Jurnal Serambi Engineering, 2025)
PT. Bumi Indo Power (BIP) will open a new pit in an area where there is still coal distribution in the mining business permit area, namely in block D of PT Bumi Indo Power, for this reason, planning for determining mining boundaries (pit limits) is needed based on the optimal Stripping Ratio value. The purpose of this study is to determine the most optimal Stripping Ratio value to obtain maximum profits using the discounted cash flow method, so that the optimum mining limit (Ultimate Pit Limit) can be determined. then make a pit plan and mining limits in accordance with the geometry recommendations, namely a tier height of 10 m, a tier width of 5 m, and a single slope of 45°. The optimization process is carried out by compiling data on stripping ratio variations that represent pit boundaries and reserves at each stripping ratio, then combined with economic considerations using a discount rate of 11.76% to obtain the Net Present Value (NPV) value, so that it can be analyzed through an optimization curve. The results of the study show that the optimum stripping ratio value obtained through the optimization curve with the Conventional NPV method in the Spot Price scenario is 8.8 with total reserves reaching 907,717 tons, a mine life of 4 years, and an NPV of IDR 285,254,334,789.00.